2020
DOI: 10.31234/osf.io/y8f4b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using tertiary sulci to map the “cognitive globe” of prefrontal cortex

Abstract: Stuss (1984) considered the human prefrontal cortex (PFC) as a “cognitive globe” on which functions of the frontal lobe could be mapped. Here, we discuss classic and recent findings regarding the evolution, development, function, and cognitive role of shallow indentations, or tertiary sulci, in PFC with the goal of using tertiary sulci to map the “cognitive globe” of PFC. First, we discuss lateral PFC (LPFC) tertiary sulci in classical anatomy and modern neuroimaging, as well as their development, with a focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 78 publications
4
36
0
Order By: Relevance
“…As such, we are not fully tied to these definitions and only emphasize that this is the first study to use surface data augmentation and context-aware training for spherical CNNs to define (i) subcomponents of the fms (mfms, ifms), (ii) subcomponents of the imfs (imfs_h, imfs_v), and (iii) subcomponents of the pmfs (pmfs_p, pmfs_i, and pmfs_a; Table 1 ). Despite contentions regarding sulcal definitions, we emphasize that the latter pmfs subcomponents are most assuredly tertiary sulci as they emerge last in gestation among sulci in LPFC ( Chi et al, 1977 ; Cunningham, 1892 ; Miller et al, 2020a ; Retzius, 1896 ; Turner, 1948 ) as well as are small and shallow compared to other sulci in LPFC ( Miller et al, 2020b ; 2020c ; Petrides, 2018 ; Voorhies et al, 2020b) as also shown in Fig. 1 .…”
Section: Experimentaldesignmentioning
confidence: 59%
“…As such, we are not fully tied to these definitions and only emphasize that this is the first study to use surface data augmentation and context-aware training for spherical CNNs to define (i) subcomponents of the fms (mfms, ifms), (ii) subcomponents of the imfs (imfs_h, imfs_v), and (iii) subcomponents of the pmfs (pmfs_p, pmfs_i, and pmfs_a; Table 1 ). Despite contentions regarding sulcal definitions, we emphasize that the latter pmfs subcomponents are most assuredly tertiary sulci as they emerge last in gestation among sulci in LPFC ( Chi et al, 1977 ; Cunningham, 1892 ; Miller et al, 2020a ; Retzius, 1896 ; Turner, 1948 ) as well as are small and shallow compared to other sulci in LPFC ( Miller et al, 2020b ; 2020c ; Petrides, 2018 ; Voorhies et al, 2020b) as also shown in Fig. 1 .…”
Section: Experimentaldesignmentioning
confidence: 59%
“…While recent studies suggest a link between the morphology of tertiary sulci in association cortices and cognitive functions, 11,20,21,25,46,51 , no study to date (to our knowledge) has tested the role of tertiary LPFC sulci in cognitive development. This gap likely persists for three key reasons.…”
mentioning
confidence: 94%
“…Due to these difficulties, very little is known regarding the role of tertiary sulci in human cognition, despite the fact that many tertiary sulci are evolutionarily new structures. We refer to tertiary sulci as evolutionarily new because they are identifiable in humans and non-human hominoids (great apes), but not in other non-human primates 9,11,[16][17][18]20,21,23,28,30 (see Supplementary Information for further details regarding dimples and lack of tertiary sulci in non-human primates).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Network variant locations are present even after surface-based normalization procedures (Fischl, 2012;Klein et al, 2010;Van Essen, 2005) that align data across people by large-scale sulcal features; with individual differences in fcMRI not well related to variations in anatomical metrics -although it is possible that they relate to finer-scale anatomical features, e.g., see (Miller et al, 2021)). This, together with correspondence to task responses, suggests that variants may relate more closely to differences in the functional positions of brain areas or systems, which can vary relative to anatomical landmarks (Frost & Goebel, 2012;Van Essen, Glasser, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%